How to prevent domestic homicides: a qualitative study of recommendations from a Canadian domestic homicide review committee - Saxton, Michael (Journal of family violence, 2025)
Purpose: Since 2003, all domestic violence-related homicides in Ontario, Canada have been reviewed by an interdisciplinary committee. This committee conducts in-depth analyses to help understand what may have been done differently, with hindsight, and make recommendations to prevent similar tragedies in the future. This study examined all recommendations made by the Ontario Domestic Violence Death Review Committee over a 10-year period (2010-2020). Methods: This study undertook a thematic analysis of all recommendations provided within 219 domestic homicide case reviews. Using a multistep coding process, several recurring themes were found across 400 recommendations. Results: Results of this study identified consistent themes related to public awareness, professional education and enhanced systems, community agency collaboration and risk assessment, safety planning, and risk management. Conclusions: These themes parallel findings by similar research studies undertaken in the United States, parts of the United Kingdom, Australia, and New Zealand. Ongoing challenges in the implementation of these recommendations and an evaluation of the impact of this work in reducing homicides is discussed.